2011
DOI: 10.1080/08911762.2011.558814
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Performance Consequences of Integrated Brand Management in China: An Exploratory Study

Abstract: This study explores the role of integrated brand management in China. Using the survey data for 309 brands, our results show that integrated brand management has a positive effect on business performance in China. We also find that top management emphasis and corporate supportive resources directly foster integrated brand management. In addition, the emphasis of top management indirectly affects integrated brand management through reward system. Furthermore, we find that these relations vary between high-and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…In the research sample, 24 articles were found (24%) which dealt with marketing strategy. Topics investigated include the following: branding (Ga et al, 2006;Bennet, 2008;Wang et al, 2009;Fu et al, 2009;Bodet, 2010;Chen et al, 2011;Chaoying et al, 2011;Leng and Zhang, 2011), distribution channels (Wing, 1994;Luk et al, 2003;Yi and Jaffe, 2007;Sternquist and Wang, 2010), pricing (Tian et al, 2005;Liu and Tang, 2005;Zhang and Zhou, 2010;Jiang et al, 2011), product positioning (Skallerud and Grønhaug, 2010), and service quality (Prugsamatz and Ofstad, 2006;Gebauer and von Zedtwitz, 2007;Stanworth, 2009). From this, it can be seen that branding was the most popular topic for authors writing about marketing strategy in China.…”
Section: Marketing Strategymentioning
confidence: 99%
“…In the research sample, 24 articles were found (24%) which dealt with marketing strategy. Topics investigated include the following: branding (Ga et al, 2006;Bennet, 2008;Wang et al, 2009;Fu et al, 2009;Bodet, 2010;Chen et al, 2011;Chaoying et al, 2011;Leng and Zhang, 2011), distribution channels (Wing, 1994;Luk et al, 2003;Yi and Jaffe, 2007;Sternquist and Wang, 2010), pricing (Tian et al, 2005;Liu and Tang, 2005;Zhang and Zhou, 2010;Jiang et al, 2011), product positioning (Skallerud and Grønhaug, 2010), and service quality (Prugsamatz and Ofstad, 2006;Gebauer and von Zedtwitz, 2007;Stanworth, 2009). From this, it can be seen that branding was the most popular topic for authors writing about marketing strategy in China.…”
Section: Marketing Strategymentioning
confidence: 99%
“…However, even though substantial works has been published about brand management, an extensive literature reveals issues related to internal factors contributing to the success of brand management based on RBV have yet to be fully covered. This "internal" brand management is crucial in brand building and management as without supportive internal processes no brand objectives can be really accomplished (Chen, Lam, & Zou, 2011). In spite of the diverse perspectives adopted in previous studies, brand management in this present study will involve three sets of variables namely antecedents, brand management, and performance outcomes.…”
Section: Theoretical Background -Resource Based View (Rbv) Theorymentioning
confidence: 99%
“…In spite of the diverse perspectives adopted in previous studies, brand management in this present study will involve three sets of variables namely antecedents, brand management, and performance outcomes. The work by Chen et al (2011) and Lee, Park, Baek, & Lee (2008) integrative model are used to develop the present study's framework.…”
Section: Theoretical Background -Resource Based View (Rbv) Theorymentioning
confidence: 99%
See 2 more Smart Citations